Optimasi Penjadwalan Mata Kuliah Menggunakan Algoritma Late Acceptence Hill Climbing Berbasis Hiper Heuristik - I Gusti Agung Premananda; Ahmad Muklason (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Course scheduling is one area of ​​operations research. This problem schedules a class without violating an existing constraint. At this time the problem of scheduling courses is becoming increasingly complex with existing limitations One of them is in International Timetabling Competition 2019 (ITC 2019) which released the latest real world dataset. This study focuses on optimizing the quality of course scheduling in order to reduce the value of the final solution of course scheduling. The algorithm used is Late Acceptance Hill Climbing (LAHC) with a hyper-heuristic approach using mutation Low Level Heuristics (LLH) and local search. The algorithm was applied to 30 ITC 2019 data sets with 100,000 iterations in 5 trials. The result is that the application of this algorithm is able to optimize with an average of 52% of the initial solution. In addition, this algorithm produces a consistent solution for 10 attempts on each dataset.